A Randomized Double-Blind, Placebo-Controlled Study to Evaluate the Anti-Skin-Aging Effect of LactoSporin – The Extracellular Metabolite from Bacillus coagulans (Weizmannia coagulans) MTCC 5856 in Healthy Female Volunteers - Majeed M; Nagabhushanam K; Paulose S; Rajalakshmi HR; Mundkur L (Clinical, Cosmetic and Investigational Dermatology, 2023)
Muhammed Majeed,1,2 Kalyanam Nagabhushanam,2 Shaji Paulose,1 HR Rajalakshmi,1 Lakshmi Mundkur1 1Sami-Sabinsa Group Limited, Bengaluru (Bangalore), Karnataka, 560 058, India; 2Sabinsa Corporation, East Windsor, NJ, 08520, USACorrespondence: Lakshmi Mundkur, Sami-Sabinsa Group Limited, 19/1& 19/2, I Main, II Phase, Peenya Industrial Area, Bengaluru, Karnataka, 560 058, India, Fax +91 8068527706, Email lakshmi@sami-sabinsagroup.comPurpose: There has been a growing interest in the use of probiotics and their products for skin care, over the last decade. LactoSporin is the extracellular metabolite of a spore-forming probiotic Bacillus coagulans (Weizmannia coagulans) MTCC 5856, with antimicrobial and skin protecting activity.Patients and Methods: The anti-skin-aging potential of LactoSporin was evaluated in a randomized, double-blinded, placebo-controlled study in healthy female participants (70 screened and 56 randomized). The participants applied either LactoSporin or matched placebo formulation (N=28 in each group) for 10 weeks, and the effects were assessed by dermatological, and non-invasive instrument-based evaluation using Antera, Cutometer, Corneometer, and Tewameter. All the 56 participants completed the study and were included for the analysis.Results: The regular use of LactoSporin cream for 10 weeks showed a significant reduction in visibility of wrinkles around crow’s feet, nasolabial folds, frown lines, and facial fine lines compared to baseline and placebo by dermatological and Antera assessments. LactoSporin showed improvement in skin elasticity and hydration by dermatological assessments, but the effect was not significantly different from placebo when assessed by Cutometer, Corneometer, and Tewameter. No adverse events or skin irritation was observed in any participants during the study.Conclusion: These results suggest that LactoSporin could be a safe natural ingredient to reduce wrinkles and fine lines in cosmetic formulations.Keywords: LactoSporin, safety, dermatological assessments, corneometer, tewameter, cutometer